Cinemática angular após artroplastia total de joelho: plataforma tibial fixa versus móvel - Amaro, Joicemar Tarouco [UNIFESP] (2016)
INTRODUCTION: Arthroplasty have been of great importance in the recovery of patients knees function when there is indication for surgical treatment. They can be divided according to the tibial component, in two types: total knee replacement tibial platform fixed and mobile platform arthroplasty. OBJETIVE: Through three-dimensional gait analysis, the angular kinematics of patients with osteoarthritis who underwent knee arthroplasty with tibial fixed and mobile platform. METHODS: We studied 64 patients randomized to two groups: group A (n = 32 - undergoing arthroplasty with fixed tibial platform) and group B (n = 32 - undergoing arthroplasty with mobile tibial platform). For the acquisition of the angular gait kinematics data, studying more specifically the movements of femorotibial axial rotation, we use the Vicon system mx 40 (oxford metrics group, UK). The kinematics was evaluated in five different activities: walking, up / down step ladder and sit / out of a chair. The rotation angles on the operated side were described according to groups with use of summary measures and compared between groups using t-student tests. RESULTS: the average angle of rotation of the patients with mobile prosthesis was statistically higher in walking, going up step and lift chair (p <0.05), just to step down and sit in the middle seat angles of rotation were statistically equal between the types of prosthesis (p = 0.160 and p = 0.209 respectively). CONCLUSION: Arthroplasty with mobile tibial platform has greater degrees of rotation when compared to the group undergoing arthroplasty with fixed platform, and this depends on the activity performed by the patient.